2023
DOI: 10.21203/rs.3.rs-2756348/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hospital readiness for the provision of care to critically ill patients in Tanzania - an indepth cross-sectional study

Abstract: Background: Critical illness is a state of ill health with vital organ dysfunction, a high risk of imminent death if care is not provided and potential for reversibility. The burden of critical illness is high, especially in low- and middle-income countries. Critical care can be provided as Essential Emergency and Critical Care (EECC) – the effective, low-cost, basic care that all critically ill patients should receive in all parts of all hospitals in the world– and advanced critical care – complex, resource-i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Worryingly, even in the midst of the COVID-19 pandemic, infection prevention and control measures remained weak. For example, in Kenya only two out of five facilities had protective face masks and aprons widely available, compounding wider problems of overcrowded, poorly maintained hospital buildings often with limited water provision 9 10. Our findings in Kenya and Tanzania are consistent with those from other low-resource settings 11…”
Section: Lessons Learnedsupporting
confidence: 78%
See 4 more Smart Citations
“…Worryingly, even in the midst of the COVID-19 pandemic, infection prevention and control measures remained weak. For example, in Kenya only two out of five facilities had protective face masks and aprons widely available, compounding wider problems of overcrowded, poorly maintained hospital buildings often with limited water provision 9 10. Our findings in Kenya and Tanzania are consistent with those from other low-resource settings 11…”
Section: Lessons Learnedsupporting
confidence: 78%
“…Our studies in Kenya and Tanzania conducted in late 2020 and in 2021 found that hospitals were generally poorly prepared to cater to the basic needs of those with critical illness 9 10. Evaluations of equipment and the human and material resources for dealing with acute, severe illness highlighted considerable variability between hospitals in such inputs and were generally lacking in Tanzania.…”
Section: Lessons Learnedmentioning
confidence: 91%
See 3 more Smart Citations